German Survey on EUS-Guided Diagnosis and Management of Gastrointestinal Stromal Tumors (GISTs) – Evidence or “Gut-Feeling”? - Jenssen, C.; Barreiros, A. P.; Will, U.; Burmester, E.; Schmidtmann, I.; Eckardt, A. J. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To examine practice patterns of endosonographers in diagnosing and managing gastrointestinal stromal tumors (GISTs) in Germany. Materials and Methods: A modified published survey (Ha et al., Gastrointest Endosc 2009) was sent to endosonographic ultrasound (EUS) customers in Germany. The survey was also publicized on the homepage of an EUS interest group. To avoid duplicate opinions, participants were asked to return one survey per institution.Results: 142 centers of roughly 850 German EUS centers responded. 25 % were from University hospitals and 74 % from community hospitals. 61 % performed > 2 EUS scans for suspected subepithelial lesions/week. Although 97 % of respondents believed that tissue acquisition with CD117 immunohistochemistry best predicts a GIST, 11 % do not perform EUS-FNA when suspecting a GIST, 68 % perform it occasionally and 18 % perform it regularly. The main EUS criteria used for a suspected GIST are the typical layer (85 %), hypoechoic appearance (80 %) and gastric location (51 %). 69 % would diagnose a GIST with negative CD117 if the EUS criteria and spindle cells are present. FNA was rated helpful in < 50 % by 55 % of participants. Size was the primary criterion for suspecting malignancy. 95 % of respondents would perform surveillance ≥ 1x/year of GISTs that are not resected. Conclusion: There is significant variability in the diagnosis and management of GISTs in Germany. Diagnostic certainty of EUS-FNA is suboptimal in many centers and EUS is frequently used for guidance. The diagnosis of a GIST is often guided by a “gut feeling” rather than evidence. Efforts should be made to unify existing guidelines.
Keywords: abdomen; stomach; endoscopy; tumor; endoscopic ultrasound; fine-needle aspiration; subepithelial tumors; gastrointestinal stromal tumor; survey